2012
DOI: 10.1159/000339225
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Red Cell Distribution Width with Glycated Hemoglobin among Healthy Adults without Diabetes Mellitus

Abstract: Background: Red cell distribution width (RDW) and hemoglobin A1c (HbA1c) are both known to be predictive of future cardiovascular disease (CVD). Objective: We hypothesized that RDW would be associated with HbA1c in adults without diabetes independent of fasting blood glucose (FBG). Methods: This cross-sectional study included 15,343 nondiabetic adults, free of CVD, enrolled in NHANES 1999–2008. Adjusted means of RDW were calculated across HbA1c categories for the overall population. Multivariable regression an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
35
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 24 publications
7
35
1
Order By: Relevance
“…We are clearly in agreement with the mounting evidence for the various associations of RDW and adverse outcomes [3,4]. Its availability and inexpensiveness make it an attractive factor to consider in the risk stratification of patients.…”
supporting
confidence: 89%
“…We are clearly in agreement with the mounting evidence for the various associations of RDW and adverse outcomes [3,4]. Its availability and inexpensiveness make it an attractive factor to consider in the risk stratification of patients.…”
supporting
confidence: 89%
“…Again in a study of V. Veranna et al examined RDW and HbA1C relation in a healthy adult. It was observed that in a healthy adult without DM, RDW is predicative of HbA1C disease development [17].…”
Section: Discussionmentioning
confidence: 99%
“…The HbA1c concentration represents the average blood glucose level over the previous three months, is free of short-term fluctuations, and can be monitored long term and controlled according to individual circumstances to an appropriate level to reduce the risk of serious complications (2). Very recently, a relationship between the elevated red blood cell (RBC) distribution width (RDW) and higher HbA1c concentrations was found in a large cross-sectional study (3).…”
Section: Introductionmentioning
confidence: 99%